Dental caries and their relation to hba1c in adults with type 2 diabetes mellitus - Deepasri Mohan; Yogesh Bhuvaneshwar; Ramakrishnan Manjankarni Jeyaram; Sukanya Saravanan; Anandakumar Amutha; Research Team (Wolters Kluwer Medknow Publications, 2022)
Diabetes mellitus with poor glycemic control is often associated with dental caries. We aim to assess the relationship between dental caries and HbA1c levels among adults with type 2 diabetes (T2D) in Chennai. A cutoff of HbA1c ≥7.0 to 7.9% (53-63 mmol/mol) was used to define Group 1 (n = 113) as moderately controlled and HbA1c ≥8.0% (64 mmol/mol) to define Group 2 (n = 228) as poorly controlled T2D. The absolute numbers of decayed, missing, and filled teeth were examined to calculate the decayed, missing and filled teeth index. Group 2 had a significantly higher percentage (48.2%) of decayed teeth when compared to Group 1 (28.3%). Group 2 had a 2.65 times higher risk of decayed teeth when adjusted for mean carbohydrate consumption, sweets consumption, oral hygiene, and brushing habit. T2D with higher HbA1c levels is associated with an increased number of decayed teeth. Hence, there is a need for monitoring dental status in T2D as earlier treatment may prevent or delay decay teeth.